Kegiatan preservasi naskah kuno Syekh Abdul Manan di Museum Bandar Cimanuk Indramayu - Ute Lies Siti Khadijah; Lutfi Khoerunnisa; Rully Khairul Anwar; Ayu Apriliani (Jurnal Kajian Informasi dan Perpustakaan, 2021)
The spread of Islam in Indramayu stems from trading activities at Cimanuk Port, Indramayu. This is completely contained in the hundred years old manuscripts of Sheikh Abdul Manan. This study aimed to determine how the preservation of Syekh Abdul Manan's ancient manuscripts at the Bandar Cimanuk Museum, Indramayu. The research used a qualitative approach through descriptive research method. Based results of research, the Bandar Cimanuk Museum has carried out activities for the preservation of Sheikh Abdul Manan’s ancient manuscripts through restrictions to direct access to museum users, routine cleaning of manuscripts and the museum environment, fumigation, and digitization. Restrictions to direct access to museum users by placing the ancient manuscripts in glass covered displays and special boxes. Routine maintenance of the museum is conducted by regulating the light and humidity, using camphor in every corner of the room, dehumidifier settings, and directing the museum visitors. Fumigation is conducted through pesticide compund to eliminate pests once a year. The digitization of ancient manuscripts into the form of a digital book (flipbook) which is carried out in collaboration with museums with various institutions, such as, a collaboration with researchers and students from Padjadjaran University. The entire process of preservation activities was carried out in a structured and panned methods. The study concludes that the importance of preservation to maintain and preserve the heritage of ancient manuscripts to be accessed and utilized by wider societies.